Oral health conditions in children 3-6 years old age of three educational institutions and the degree of oral health knowledge, their parents and teachers - Tamayo Vargas, Cecilia (2013)
The purpose of the study was to determine the oral health conditions of children in three educational institutions and the level of knowledge of parents and teachers. The study was descriptive and transversal. Done in 110 schoolchildren, 56 boys and 54 girls aged 3-6 years , and 69 parents and teachers from three educational institutions of human settlement “Los Olivos Peace “ Window -Lima . Children findings were recorded in a medical record , according to the WHO criteria for dental caries and oral hygiene , and a questionnaire was administered to parents and teachers to determine the level of knowledge of oral health. The results were: caries prevalence of 90 %, dmft of 5.1 (95% CI 4.4 to 5.8 ), regular hygiene of 66 % , and statistically significant association between children with 100 % prevalence of cavities whose parents have higher education (p = 0.000) and 87 % prevalence of caries in children with parents of secondary education . The questions were less successful in the area of preventive methods: fluoride-containing foods (32 %) and “use of sealants” (33%). It was determined that the oral health condition of children is bad for the presence of caries and need for oral hygiene and health knowledge of parents and teachers is low and needs to be reinforced.